Adaptation of the organizational strategy of the learning evaluation system in the internal medicine wards round performance. - Luis Alberto Corona Martínez; Juan Rivero Berovides (Medisur)
After having identified the difficulties in the development of abilities in the first state exam of medicine, the members of the Medical Clinical Department carried out some innovations in the system of evaluation in Internal medicine which included the introduction of computarized simulations as a way to assess the residents partially in the subject and the substitution of the objectively structural clinical exam of the final test for an integral exam of performance and a written test. The changes were put into practice from 1999 to the year 2000 and it was observable that the results of the exam of performance of the second state exam were superior. There was also an improvement in the results of the state exam when compared with the other exams. This strategy offers a more real and objective certificate of the resident´s competence in the fulfilment of their professional tasks and stimulates a process of learning directed to guarantee the application of knowledge and to form the students integrally